Improving Learning Achievement of Class IV Students in Social Lessons About Natural Views By Using Interactive Learning Model - Sri Mulyati (Eduvest - Journal of Universal Studies, 2021)
The problem that arises in schools when carrying out student learning in the social sciences field is the lack of motivation from students in participating in the teaching and learning process. This study aims to provide input or information to improve the quality of the process or learning outcomes in the classroom by appealing to teachers to do CAR. This study uses a qualitative methodology, namely classroom action research. The place used to carry out this research is SD Negeri Pondok Kacang Timur 04 Pondok Aren District. The time used by researchers in carrying out this classroom action research was for 2 cycles, namely on October 15, 2019 (Cycle 1) and October 22, 2019 (Cycle 2). The research subjects were students of Pondok Kacang Timur 04 Elementary School Class IVB, totaling 23 students. Based on the description of the discussion and the results of the research, it can be concluded that from Cycle 1 to cycle 2 regarding the use of interactive learning models, the authors can conclude that by using interactive learning, it is able to improve the learning achievement of fourth grade students of SD N Pondok Kacang Timur 04 on material about natural appearances. Through interactive learning, students can be more active in learning activities, especially in social studies subjects.